KAJIAN LITERATUR SISTEMATIS: PERAN VISUAL THINKING DALAM PEMECAHAN MASALAH MATEMATIKA - Efi Ismauliani; Seni Yanti; Anwar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Visual thinking refers to the ability to think using visual representations such as images, diagrams, and schemes to support the process of solving mathematical problems. This ability is considered important in helping students solve various mathematical problems that require reasoning and problem-solving strategies at all levels of education. This systematic literature review aims to analyze various research findings regarding the role of visual thinking in mathematical problem solving published from 2020 to 2026. The method used in this study was a Systematic Literature Review (SLR) by analyzing 15 accredited national journal articles indexed in Sinta and international indexed journals. The findings indicate that visual thinking has a positive effect on students’ mathematical problem-solving abilities at various educational levels, particularly in understanding problems and planning solution strategies. Learning approaches that apply visual methods have been proven to improve students’ representation skills, reasoning abilities, and self-confidence in mathematics learning. Therefore, the systematic development of visual thinking in mathematics learning needs to be enhanced so that students can understand concepts more easily and solve mathematical problems more effectively.